We have quadratic equation
"a^2-a(2bcos(y))+b^2-c^2=0"
Using quadratic formula
"a_{1,2}=bcos(y)\u00b1\\sqrt{b^2cos^2(y)-b^2+c^2}"
"a_{1,2}=bcos(y)\u00b1\\sqrt{-b^2(1-cos^2(y))+c^2}"
"a_{1,2}=bcos(y)\u00b1\\sqrt{-b^2sin^2(y)+c^2}"
So this is not strict equivalence:
"if\\ a=bcos(y)+\\sqrt{c^2-b^2sin^2(y)},\\"then a is the root of the equation
"c^2=a^2+b^2-2abcos(y)"if a is the root of the equation
then
or
Comments
Dear Fareedat, You're welcome. We are glad to be helpful. If you liked our service please press like-button beside answer field. Thank you!
Thanks for the solution...I really appreciate
Leave a comment